O território como espaço de inclusão: desafios e possibilidades na vida cotidiana de uma criança autista - Roque, Franciele Isabelle Reis (Universidade Federal de São Carlos, 2025)
Autism, historically conceived from different perspectives, is increasingly being understood in light of the neurodiversity movement, which recognizes it as a natural variation of the human condition. Despite advances in public policies and the recognition of their rights, the process of social inclusion of autistic children remains a challenge, considering the structural, cultural, and attitudinal barriers. In this scenario, it becomes relevant to investigate how inclusion occurs in the life territories of these children, from the perspective of psychosocial care, which values ​​the singularities of the subjects and the collective, social, and cultural dimensions involved in care. Thus, this study aimed to identify and understand the process of social inclusion of an autistic child in their territory, considering the perspective of the child and their caregivers. The research, of a qualitative nature, is characterized as a case study, involving an autistic child and their caregivers. Data production took place over six months, using participant observation, field diary, semi-structured interviews, and creative methodologies. Data analysis was performed using ATLAS.ti software and a holistic case analysis, based on a detailed description of the child's and their family's experiences. This process included identifying central themes, organized into three axes: 1) Characterization of the Participants; 2) Daily life and social inclusion: possibilities from the territory; and 3) Barriers and challenges to social inclusion in the territory. The results show that social inclusion depends on both effective public policies and a sensitive and welcoming community network that recognizes human diversity. The study contributes to strengthening intersectoral practices and policies that broaden access and social participation of autistic children in their territories.
The territory as a space for inclusion: challenges and possibilities in the daily life of an autistic child
Keywords: Inclusão social; Autismo; Crianças; Atenção psicossocial; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; 3. Saúde e Bem-Estar